Development and use of Vitafert in the agricultural sector - Valiño Cabrera, Elaine C.; García Hernández, Yaneisy; Bustamante García, Daymara; Beruvides Rodríguez, A. (Cuban Journal of Agricultural Science, 2024)
At Instituto de Ciencia Animal (Cuba), an additive called Vitafert was obtained, with probiotic activity, for animal production. This review mainly deals with the aspects related to the process for the development of this zootechnical additive, which includes microbial inoculants, percentages of raw matters used, the production process, technological variants and its use in the agricultural sector. Information about the progress made with this zootechnical additive is also collected, with positive effects on physiological, immunological, health and production indicators of different species of economic interest. Due to its importance, it is proposed to continue the researchers carried out with Vitafert, with the aim of improving its production and optimization process, as well as the mechanisms of action that generate beneficial responses in animals, based on advanced technologies in health and nutrition.